2020
DOI: 10.3390/cancers12040975
|View full text |Cite
|
Sign up to set email alerts
|

Management of HPV-Related Squamous Cell Carcinoma of the Head and Neck: Pitfalls and Caveat

Abstract: Head and neck squamous cell carcinomas (HNSCCs) are a very heterogeneous group of malignancies arising from the upper aerodigestive tract. They show different clinical behaviors depending on their origin site and genetics. Several data support the existence of at least two genetically different types of HNSCC, one virus-related and the other alcohol and/or tobacco and oral trauma-related, which show both clinical and biological opposite features. In fact, human papillomavirus (HPV)-related HNSCCs, which are ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 62 publications
1
40
0
Order By: Relevance
“…It is also worth to notice, that in all meta-analyses regarding relation between HPV infection and prognosis, this relation was tested irrespectively of treatment type [4][5][6][7]. Therefore, other factors, including stimulation of immune response through viral infection and/or beneficial epidemiological and clinical features (younger age, white race, better performance status, no addiction to nicotine and alcohol) of HPV positive patients may be responsible for better prognosis [3]. Summarizing this part of discussion, it seems that OPSCC patients with HPV positivity respond better to CisPt-CRT, however, the results of research aimed at explaining mechanisms related to this observation are inconclusive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also worth to notice, that in all meta-analyses regarding relation between HPV infection and prognosis, this relation was tested irrespectively of treatment type [4][5][6][7]. Therefore, other factors, including stimulation of immune response through viral infection and/or beneficial epidemiological and clinical features (younger age, white race, better performance status, no addiction to nicotine and alcohol) of HPV positive patients may be responsible for better prognosis [3]. Summarizing this part of discussion, it seems that OPSCC patients with HPV positivity respond better to CisPt-CRT, however, the results of research aimed at explaining mechanisms related to this observation are inconclusive.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggest that there may be a subpopulation of cancer stem cells (CSCs), which simultaneously exhibit unlimited ability to self-renew and differentiate towards neoplastic cells [2]. However, with regard to prognosis of HNSCC patients, it should be taken into account that, as was shown in many studies (for review see [3]) and meta-analyses [4][5][6][7], better prognosis is related to Human Papillomavirus (HPV) infection. This infection (most often with HPV16) is currently considered an important etiological factor in the development of squamous cell carcinoma of the oropharynx (OPSCC) [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…This case suggests that the combination of surgery and subsequent application of topical 5% imiquimod may reduce the risk of relapses when surgery has not been radical, proposing an alternative treatment in elderly patients or in areas where surgical enlargement may be cosmetically unacceptable, has been refused, or is not possible. Testing SCC for HPV positivity may help select the better treatment available, as HPV-related SCC is usually less invasive [8]. This kind of treatment could also be proposed to selected patients with a superficial disease, no risk of metastasis, and when standard care has been refused or is not possible.…”
Section: Discussionmentioning
confidence: 99%
“…HPV 16 accounts for 90% of cases. HPV-associated cancers tend to have increased survival and better outcomes [8], although SCC affecting the perioral region tends to have a worse prognosis than other types of SCC [9].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that virus-related HNSCCs possess peculiar clinical and biological features. Perri et al described the molecular differences and similarities between HPV-negative and HPV-positive HNSCC including the better prognosis and response to therapies of the latter group of patients [ 15 ]. Remarkably, patients with HPV-driven HNSCCs are frequently more responsive to conservative treatments and immunotherapy, opening questions about the use of pre-therapy assessment in order to guide the treatment strategy.…”
mentioning
confidence: 99%